2016
DOI: 10.18488/journal.61/2016.4.2/61.2.55.70
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Gifted Students at King Abdullah II Schools for Distinction: Students Perspective

Abstract: The study aims at recognizing the problems which gifted students at King Abdullah II Schools for Distinction (KASD) face.The study sample, 240 male and female students, is randomly selected out of the gifted students with a percentage of 50 % of the study society. A forty item questionnaire is prepared to achieve the study objectives. It is distributed into three fields: Problems related to school, to family, and to students. Study results show that problems which KASD students face are rated medium.Problems r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Naturally, this varies depending on everyone's circumstances, including those surrounding the gifted person, such as parents, teachers, and school administration. (Ayasreh & El-Omari, 2016) classified their problems into: Internal Problems: These include imbalances in mental and physical growth, emotional and intellectual growth, heightened sensitivity and selfaccountability, existential philosophy, diverse interests, and an inclination to establish systems and laws at an early age.…”
Section: Sources Of Gifted Students' Problemsmentioning
confidence: 99%
“…Naturally, this varies depending on everyone's circumstances, including those surrounding the gifted person, such as parents, teachers, and school administration. (Ayasreh & El-Omari, 2016) classified their problems into: Internal Problems: These include imbalances in mental and physical growth, emotional and intellectual growth, heightened sensitivity and selfaccountability, existential philosophy, diverse interests, and an inclination to establish systems and laws at an early age.…”
Section: Sources Of Gifted Students' Problemsmentioning
confidence: 99%
“…There was no time for extracurricular activities, and students often felt lazy, as the curriculum focused on memorization, although normal students' teaching methods had been used (Ayasreh & El-Omari, 2016). That is why this study intends to detect the effect of the blended learning based training program (BLBTP) in developing the creative thinking skills (CTSs) of gifted students of KASD, and also constructing a BLBTP.…”
Section: Study Problem and Objectivesmentioning
confidence: 99%
“…The results found that the degree of self-confidence for students is high, and there was a positive relationship between self-confidence and achievement in favor of males, and self-confidence is considered a good predictor of academic achievement. Ayasreh et al (2016) identified the high achieving students' problems at King Abdullah II Schools for Distinction (KASD). The sample size was 240 male and female students who answered a questionnaire distributed into three fields: Problems related to school, family, and students.…”
Section: Introductionmentioning
confidence: 99%